Tindakan Bedah Darurat ditengah Keterbatasan : Studi Kasus Banjir Bireun, Aceh - M. Raisya Kesha; Zumirda Zumirda (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Floods are the most frequent hydrometeorological disasters in Indonesia and significantly contribute to increased trauma cases and disruption of healthcare services, particularly in vulnerable regions such as Aceh Province. These conditions are exacerbated by limited resources, damaged health facilities, and restricted access to referral centers. This study aims to examine the implementation of early emergency surgical management during flood disasters based on damage control surgery principles and international guidelines. A descriptive qualitative approach was employed through a literature review combined with field observations conducted during the emergency response phase of flood disasters in Bireuen Regency. Data were collected from direct clinical observations, brief interviews with healthcare providers, and documentation of trauma cases requiring early surgical intervention. The results indicate that effective patient stabilization can be achieved despite limited resources through airway, breathing, and circulation (ABC) management, hemorrhage control, wound irrigation, and fracture immobilization using simple and improvised equipment. Approximately 90% of patients were successfully stabilized prior to referral to definitive healthcare facilities. In conclusion, adaptive and timely application of damage control surgery principles plays a crucial role in saving lives and strengthening emergency surgical response during flood disasters.